2005
DOI: 10.1116/1.1943445
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic strain fields in granular GaAs:MnAs epitaxial layers: Towards self-assembly of magnetic nanoparticles embedded in GaAs

Abstract: Adjusting the magnetic properties of semiconductor epilayers by the crystallographic orientation of embedded highly anisotropic magnetic nanoclusters Granular GaAs:MnAs, consisting of MnAs nanoclusters embedded in a GaAs matrix, is a hybrid ferromagnet-semiconductor material with potential applications in information storage, magneto-optical, and spin electronics devices. It can be obtained, through phase separation, by high-temperature annealing of diluted ͑Ga,Mn͒As films grown by molecular-beam epitaxy. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 38 publications
2
19
0
Order By: Relevance
“…43 It has been theoretically shown that reduction of misfit stresses tends to cause the preferred crystal lattice orientations of nanoparticles in a composite film. We propose that these changes arise as a result of the nearly tenfold difference between the thermal expansion coefficients of MnP and GaP, thereby considerably modifying the lattice misfit at the matrix/cluster interfaces for different growth temperatures.…”
Section: A Growth Modelmentioning
confidence: 99%
“…43 It has been theoretically shown that reduction of misfit stresses tends to cause the preferred crystal lattice orientations of nanoparticles in a composite film. We propose that these changes arise as a result of the nearly tenfold difference between the thermal expansion coefficients of MnP and GaP, thereby considerably modifying the lattice misfit at the matrix/cluster interfaces for different growth temperatures.…”
Section: A Growth Modelmentioning
confidence: 99%
“…[23][24][25][26] After HT annealing, the difference between the lattice constant of the layer originally constituting the (Ga,Mn)As ternary alloy and the lattice constant of the GaAs substrate is due only to strain in the GaAs host lattice caused by the presence of Mn-rich clusters. [27][28][29] The clusters themselves do not contribute to the diffraction peaks shown in Fig. 1.…”
Section: Structural Propertiesmentioning
confidence: 99%
“…It is known from previous reports, that Mn-rich nanocrystals can exert a compressive strain on a surrounding GaAs matrix. [27][28][29] Since the in-plane lattice parameter of the layer is fixed to shows the strain calculated from the lattice constants obtained from angular positions of diffraction peaks shown in Fig. 1.…”
Section: Structural Propertiesmentioning
confidence: 99%
See 2 more Smart Citations